PERLINDUNGAN HUKUM TERHADAP PELANGGARAN HAM YANG TERJADI PADA ANAK BUAH KAPAL (ABK) - Agnescia, Pera; Jamba, Padrisan (LPPM Universitas Putera Batam, 2024)
Indonesia, a major contributor of labor in the fisheries sector, particularly as fishery crew members (ABK),faces challenges where ABK on both domestic and foreign vessels often fall victim to various forms of abuse,including violence, forced labor, and human trafficking. This study adopts a normative approach using a legalmethod to analyze regulations and aims to investigate the main issues confronting the Indonesian fisheriesworkforce, specifically ABK. Research findings reveal inadequate protection due to factors such as insufficientsectoral policies, delays in formulating and implementing regulations, lack of awareness, inadequate datacollection, weak policy enforcement, and limited government attention. To address these challenges, the studyrecommends comprehensive protection involving the fulfillment of basic labor rights and the implementationof capacity development initiatives. Capacity enhancement can be achieved through fiscal policies, operationalsupport, and broader access to information about fishery product usage. Consequently, protection policies forworkers in the capture fisheries sector should be comprehensive, considering economic, legal, and socialaspects across various related sectors.